2019
DOI: 10.22437/ifstj.v2i1.6077
|View full text |Cite
|
Sign up to set email alerts
|

A Study On Physicochemical And Sensory Characteristics Of Eggless Yellow Cake

Abstract: To evaluate the practicability of full substitution of eggs in production of a cake, different concentrations (0.5%, 1.0% and 1.5%) of xanthan gum were used. The results showed that substituting eggs with 0.5% xanthan gum inside a cake produced a harder cake and lower its moisture content, water activity and volume compared to control (1599.66 and 1945.69 g, 28.87 and 26.97%, 0.91 and 0.89, 523.33 and 425.00 cm3, respectively). The sensory evaluation result showed that the addition of 0.5% xanthan gum to an eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For cohesiveness, the egg muffin had the lowest values (100.50%) compared with eggless muffins (126.47%–187.60%). Incorporating hydrocolloids in muffins tends to increase their cohesiveness due to their gelling properties, which reduces the internal resistance within the crumb, making it stick to itself (Azmi et al ., 2018; Olawuyi & Lee, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For cohesiveness, the egg muffin had the lowest values (100.50%) compared with eggless muffins (126.47%–187.60%). Incorporating hydrocolloids in muffins tends to increase their cohesiveness due to their gelling properties, which reduces the internal resistance within the crumb, making it stick to itself (Azmi et al ., 2018; Olawuyi & Lee, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Azmi et al . (2018) reported that a higher xanthan gum concentration in eggless cake increased its springiness. For cohesiveness, the egg muffin had the lowest values (100.50%) compared with eggless muffins (126.47%–187.60%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation